2016
DOI: 10.1073/pnas.1603488113
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of the ternary complex that mediates termination of NF-κB signaling by IκBα

Abstract: The transcription factor NF-κB is used in many systems for the transduction of extracellular signals into the expression of signal-responsive genes. Published structural data explain the activation of NF-κB through degradation of its dedicated inhibitor IκBα, but the mechanism by which NF-κB-mediated signaling is turned off by its removal from the DNA in the presence of newly synthesized IκBα (termed stripping) is unknown. Previous kinetic studies showed that IκBα accelerates NF-κB dissociation from DNA, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 27 publications
2
16
1
Order By: Relevance
“…In the current study, these phosphatases were determined, and it was found that PP4C, PP4R3β, PP4R2, PP2ACα, and PP2A were elevated by ZnO NPs in embryos (Figure 2D). Transcription factor NF-κB (nuclear factor-kappa B) is a critical regulator of multiple biological functions: cell growth, cell survival, innate and adaptive immunity, and others [101104]. In the current study it was found that ZnO NPs treatment decreased NF-κB in embryos.…”
Section: Discussionsupporting
confidence: 50%
“…In the current study, these phosphatases were determined, and it was found that PP4C, PP4R3β, PP4R2, PP2ACα, and PP2A were elevated by ZnO NPs in embryos (Figure 2D). Transcription factor NF-κB (nuclear factor-kappa B) is a critical regulator of multiple biological functions: cell growth, cell survival, innate and adaptive immunity, and others [101104]. In the current study it was found that ZnO NPs treatment decreased NF-κB in embryos.…”
Section: Discussionsupporting
confidence: 50%
“…We previously showed that DNA binding could be monitored by observing the 1D 1 H spectrum of the distinctive imino resonances of the DNA (13). We used this technique to monitor the formation of the ternary NFκB-DNA-IκBα(5xPEST) complex and found that the complex was fully formed at a slight excess (1. chemical-shift perturbations, amide resonances also disappeared upon the formation of the ternary complex; the great majority of the missing peaks were in AR3 (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Discussion IκBα(WT) efficiently strips NFκB from DNA (6,11). The mechanism of this process necessitates the formation of a ternary complex, which was extremely transient under stopped-flow conditions but could be observed under the high-concentration conditions of NMR experiments (11)(12)(13). Using coarse-grained simulations, we showed that at least part of the driving force for molecular stripping likely comes from electrostatic repulsion between the negatively charged IκBα PEST sequence and DNA (25).…”
Section: Stripping-impaired Iκbα Is Deficient In Regulating Nfκb In Kmentioning
confidence: 92%
See 2 more Smart Citations